Физическое развитие детей с патологией щитовидной железы - Иванова, Ф.Е. (Таврический медико-биологический вестник, 2010)
Обстежено 138 дітей. Виявлено, що для фізичного розвитку дітей з патологією щитовидної залози характерно зниження середніх показників у дівчат з аутоімунним тиреоїдитом та у хлопчиків і дівчат з дифузним зобом. 138 children were examined. It is detected, that the physical development of children with thyroid body pathology is strongly connected with the decline of average index: girls with autoimmune thyroiditis and boys and girls with diffuse toxic struma.